1995
DOI: 10.1016/0191-2615(95)00016-7
|View full text |Cite
|
Sign up to set email alerts
|

An augmented lagrangean dual algorithm for link capacity side constrained traffic assignment problems

Abstract: As a means to obtain a more accurate description of traffic flows than that provided by the basic model of traffic assignment, there have been suggestions to impose upper bounds on the link flows. This can be done either by introducing explicit link capacities or by employing travel time functions with asymptotes at the upper bounds. Although the latter alternative has the disadvantage of inherent numerical ill-conditioning, the capacitated assignment model has been studied and applied to a limited extent, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 35 publications
(63 reference statements)
2
114
0
1
Order By: Relevance
“…2 Branston (1976) and Larsson and Patriksson (1995) argue that functions of that kind are unrealistic in the sense that the resulting travel times are finite whenever the arc flows are finite, so that the arcs are actually assumed to be able to carry arbitrarily large volumes of traffic flows; in practice, however, road links have some finite limits on traffic flows. Moreover, they point out that travel times predicted in the overloaded range do not have a real meaning.…”
Section: Network With Capacitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Branston (1976) and Larsson and Patriksson (1995) argue that functions of that kind are unrealistic in the sense that the resulting travel times are finite whenever the arc flows are finite, so that the arcs are actually assumed to be able to carry arbitrarily large volumes of traffic flows; in practice, however, road links have some finite limits on traffic flows. Moreover, they point out that travel times predicted in the overloaded range do not have a real meaning.…”
Section: Network With Capacitiesmentioning
confidence: 99%
“…Boyce, Janson, and Eash (1981) have empirically found that asymptotic travel time functions yield unrealistically high travel times and devious rerouting of trips. In addition, Larsson and Patriksson (1995) criticize the inherent numerical ill conditioning of this approach. They go on to exalt the extension of the basic model by including explicit arc capacities as an interesting alternative to the use of asymmetric traffic assignment models, where such extensions are made through the development of complex travel cost functions, which, in practical applications, are difficult to calibrate.…”
Section: Network With Capacitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A VI model was proposed by Chen et al (2011) to formulate the DUE problem with side constraints. Taking as a simple case of the side constraints, the link capacity constraints problem in the context of DUE has also been widely investigated, see, e.g., Larsson and Patriksson (1995), Nie et al (2004).…”
Section: Literature Reviewmentioning
confidence: 99%